Tax compliance dilemma among TikTok sellers in Malaysia / Norizam Ahmad @ Muhammad and Fa'izah Ghazi - Ahmad @ Muhammad, Norizam; Ghazi, Fa'izah (Fakulti Perakaunan, 2023)
The rise of social media platforms such as TikTok has had a significant impact on the way businesses operate. In Malaysia, a growing number of businesses are using TikTok to sell their products and services. This has led to a need for a better understanding of the factors that influence tax compliance among TikTok sellers. The rise of e-commerce has also created new challenges for tax authorities, who must ensure that all businesses, regardless of their size or mode of operation, comply with tax laws and regulations.